Financing Relations Of MSME And Non-MSMEs, Number Of Syariah Bank Offices To Gross Regional Domestic Product - Darma Taujiharrahman; Rahman El-Junusi; Zuhdan Ady Fataron (Universitas Islam Negeri (UIN) Walisongo Semarang, 2021)
AbstractPurpose - This study aims to analyse the relations of financing of MSME, non-MSMEs and the number of offices on Gross Regional Domestic Product of Central Java Province during 2014-2019.Method - This research is using The comparative causal research method which one of the ex post-facto quantitative research methods carried out by looking at the causal relationship between one change and another based on existing data.Result - The result of this research indicates that the financing of MSME and non-MSMEs had positive and significant effect on Gross Regional Domestic Product of Central Java Province during 2014-2019 and the number of offices had negative non-significant effect on Gross Regional Domestic Product of Central Java Province during 2014-2019.Implication - This study uses the data from Islamic bank in Central of Java and the Gross Regional Domestic Product of Central Java.Originality- The paper looks into the relations of the financial inclusion that provided by Islamic banks to the public in order to support the creation of economic growth in Central Java. The number of offices discribed the access to Islamic banks and the financing of MSME and non-MSMEs discribed the usage of Islamic banks in Central Java.